Collectivism culture and green transition: An empirical investigation for the rice theory - Qu, Danxue (Frontiers in Environmental Science, 2023)
With growing concerns worldwide on global warming, emissions reduction has become a major challenge for many countries. China, as the largest carbon emitter, has played a key role in achieving global green transition. Using panel data from 2004-2017 on 31 Chinese provinces, this study examines the relationship between the collectivism culture and green transition. My results reveal that places with a stronger collectivism culture tend to make more green investments, and the results remain valid after a battery of robustness tests. In addition, heterogeneity analysis indicates that the positive effects of collectivism culture on green investments are more pronounced if the province governor is advanced in age, well educated, and holds a long tenure. Additionally, such effects are more conspicuous in those provinces with more serious pollution, greater levels of collectivism, and more developed markets. This study fills a theoretical gap in the field of research on green investments from a cultural perspective. Therefore, this study has important implications for promoting green development and achieve carbon peaking and neutrality.